Oncologic and surgical outcomes for gastric cancer patients undergoing gastrectomy differ by race in the United States. Issue 10 (October 2020) - Tee, May C.; Pirozzi, Noah; Brahmbhatt, Rushin D.; Raman, Shankar; Franko, Jan
Abstract: Introduction: Gastric adenocarcinoma lymph node retrieval during gastrectomy and survival differ significantly between Asian and Western studies. It is unclear whether such disparities are the result of surgical technique, patient population, or other factors. In this observational study, we aimed to determine whether lymph node retrieval and outcomes differ between White, Black, and Asian American patients undergoing gastrectomy for adenocarcinoma. Materials and methods: 47, 217 cases of gastric resection for gastric adenocarcinoma and its subtypes were identified in the National Cancer Data Base (2000–2015). Differences in demographics, lymph node retrieval, operative outcomes, and survival were compared by self-reported race (White, Black, and Asian). Results: Asians had greater median lymph node retrieval (17) compared to White (15) and Black (16) patients, P < 0.001. Lymph node ratio was lowest in Asian (0.03) compared to White (0.05) and Black (0.09) patients, P < 0.001. Postoperative mortality was lowest in Asian patients on multivariable analysis (90-day mortality adjusted odds ratio of 0.54, P < 0.001). Median survival was not yet reached for Asian patients but was 39.5 months for White and 43.0 months for Black patients (P < 0.001). Differences in survival by race persisted on multivariable analysis (Asian adjusted hazard ratio was 0.64, 95% CI: 0.59–0.70, P < 0.001). Conclusions: Asian-American patients with gastric cancer undergoing gastrectomy have greater lymph node retrieval, decreased lymph node ratio, decreased postoperative mortality, and increased long-term survival compared to White or Black Americans. Data suggest factors other than surgical technique and oncologic care may be responsible for gastric adenocarcinoma outcome differences seen between Asian and Western studies.